2017
DOI: 10.1002/mnfr.201601003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary total flavonoids intake and risk of mortality from all causes and cardiovascular disease in the general population: A systematic review and meta‐analysis of cohort studies

Abstract: The meta-analysis provides strong evidence for the recommendation of consuming flavonoids-rich food to reduce risks of mortality from all causes as part of a healthy diet among general adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Our study cohort had a median age of 56 years (IQR 52-60) at entry and a median follow-up of 21 years (15)(16)(17)(18)(19)(20)(21)(22). During a total of 939 031 person-years of followup, 8773 individuals were admitted to hospital for any atherosclerotic cardiovascular disease, 5323 for ischaemic heart disease, 2920 for ischaemic stroke, and 1867 for peripheral artery disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study cohort had a median age of 56 years (IQR 52-60) at entry and a median follow-up of 21 years (15)(16)(17)(18)(19)(20)(21)(22). During a total of 939 031 person-years of followup, 8773 individuals were admitted to hospital for any atherosclerotic cardiovascular disease, 5323 for ischaemic heart disease, 2920 for ischaemic stroke, and 1867 for peripheral artery disease.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoid intake in Denmark is similar to intakes reported for other European countries and generally lower than intakes reported for the UK, because of a lower average consumption of tea. 13 In the past few years, studies assessing the relationship between flavonoid intake and cardiovascular disease have focused primarily on mortality from any cardiovascular disease 18 or coronary heart disease and ischaemic stroke, both indivi dually and combined. 19,20 A 2017 meta-analysis found that total flavonoid intake was marginally, but not significantly, associated with a lower risk of cardiovascular disease mortality (relative risk 0·85, 95% CI 0·70-1·03) for the highest versus lowest category of total flavonoid intake; 18 similar risk estimates have been reported in other meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are usually provided to the food as color, flavor, bitter, and astringent, and maintain stability from oxidation. Several epidemiological studies and associated meta-analyses strongly showed that the consumption of these polyphenols offered better protection against chronic diseases such as cancers, cardiovascular diseases, cerebrovascular diseases, diabetes, ageing and neurodegenerative diseases [2,3,4,5]. …”
Section: Polyphenolsmentioning
confidence: 99%
“…The fact that SSBs contain added sugars and pure fruit juice contains natural sugars could be one of the possible explanations for the different associations with all-cause mortality. Furthermore, in contrast to SSBs, pure fruit juice contains polyphenols which are associated with a lower all-cause mortality risk [4]. ASBs also initially appeared to be associated with all-cause mortality in the highest intake category (more than two ASBs per day).…”
Section: The Uk Biobank Studymentioning
confidence: 98%